MENINGKATKAN KEMAMPUAN KOGNITIF ANAK KELOMPOK B MELALUI PEMBELAJARAN SCIENCE TECHNOLOGY ENGINEERING ART MATHEMATICS (STEAM) - Fatimah, Eulis Siti; Riyanto, Arifah A; Rohmalina, Rohmalina (IKIP Siliwangi, 2021)
Cognitive aspects at the age of 0–6 years are the most important part of children's development, this aspect includes learning and problem-solving, logical thinking, and symbolic thinking. The cognitive theory developed by scientists Piaget and Lev Vygotsky states that a child's knowledge can be obtained from an environment that requires adult guidance (scaffolding), so the role of the teacher is very important because in schools teachers guide and stimulate children's cognitive abilities. The teacher also arranges the lesson so that it attracts attention and the child does not get bored easily. Group B children in PAUD Assurur were less interested in cognitive learning because they considered it less attractive. Learning STEAM is one of the methods used in the learning process to improve the cognitive abilities of children in group B. The purpose of this study is to determine the learning activities of STEAM that can improve children's cognitive abilities. Group B. This research uses a qualitative approach with descriptive research methods. The research data was carried out using observation and interviews. The results showed that children had a significant improvement. With the STEAM learning process, children are excited to learn because it is very fun and interesting. In addition to being fun and interesting for children, learning STEAM also uses media that makes children not easily bored so that learning STEAM can improve the cognitive abilities of group B.Aspek kognitif pada usia 0–6 tahun adalah bagian yang terpenting bagi perkembangan anak, aspek ini mencakup belajar dan pemecahan masalah, berpikir logis dan berpikir simbolis. Teori kognitif yang dikembangkan oleh ilmuwan PiagetdanLev Vygotskyyang menyatakan tentang pengetahuan seorang anak dapat diperoleh dari lingkungan yang membutuhkan bimbingan orang dewasa (scaffolding). Menstimulasi kognitif anak harus dilakukan oleh dengan cara menyusun pembelajaran sedemikian rupa sehingga akan menarik perhatian anak. Penelitian ini bertujuan untuk mengetahui pengaruh kegiatan pembelajaranSTEAMterhadap peningkatan kemampuan kognitif anak kelompok B. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian deskriptif. Data penelitian dilakukan dengan cara obsevasi dan wawancara. Teori Miles dan Huberman digunakan untuk menganalisis data dimulai dari reduksi data, penyajian data dan verifikasi. Hasil penelitian menunjukkan bahwa ada peningkatan kemampuan kognitif untuk beberapa indikator pada 4 orang anak, hal tersebut dapat dilihat dari hasil penilaian yang asalnya masih BB berubah menjadi MB dan yang asalnya dari MB berubah menjadi BSH.Dengan proses pembelajaran STEAManak-anak menjadi semangat untuk belajar karena sangat menyenangkan dan menarik sehinnga dapat meningkatkan kemampuan kognitif kelompok B.